INFLUENCE OF EXTERNAL FUNDING ON RETURN ON ASSETS IN LIPPO GROUP COMPANY - Isna Ardila; Darma Yanti (AIBPM Publisher, 2019)
Return on Assets as one form of the ratio of profitabiltas to measure the ability of a company with the overall funds infused in assets used to operate the company in generating profits. The purpose of this research is to analyze influence external funding as measured by the Debt Equity Ratio on Return on Assets in the Lippo Group Company. Population in this research are Lippo Group Company that listed on the Indonesia stock exchange period 2013 – 2017. Samples are taken by using saturation sampling method. It used 7 companies as sample in Lippo Group period 2013 – 2017, So total observation in this research are 35 observations. Types and sources of data in this research is quantitative data and secondary data. The using of analyzed method is by simple linear regression using Statistical Package for the Social Sciences (SPSS). Hypothesis testing are using t test. The results of this research show that External Funding as measured by Debt Equity Ratio influence Return on Assets significantly in Lippo Group Company that listed in the Indonesia stock exchange.